2014
DOI: 10.4103/0973-1296.137358
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toad skins Bufo bufo gargarizans Cantor from different regions for their active constituents content and cytotoxic activity on lung carcinoma cell lines

Abstract: Background:The skin of Bufo bufo gargarizans Cantor, rich in bufadienolides, peptides, and alkaloids, has approved pharmacological activity for preliminary anti-liver and lung tumor treatment. However, few studies have systematically focused on the influence of the producing regions on the content and antitumor activity of the active constituents in toad skins.Objective:This study aims to compare toad skins obtained from six different regions in China (Jiangsu, Anhui, Henan, Hebei, Jiangxi, and Shandong provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Being listed in the Chinese Pharmacopeia, Bufonis venenum has been used as a therapeutic agent in Asian countries for centuries to treat cardiovascular diseases, inflammatory diseases, cancers and chronic pain [12,70,80,87,88,91]. The major active components in Bufonis venenum are bufadienolides, such as cinobufagin, bufalin, resibufogenin, cinobufotalin, bufotenine, bufotenidine, and bufobutanoicacid, the first three of which account for approximately 10% of the dry weight of toad venom [43,46,47,84,86]. The antiinflammatory and antinociceptive effects of Bufonis venenum and its purified bufadienolides have been extensively studied over the past years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being listed in the Chinese Pharmacopeia, Bufonis venenum has been used as a therapeutic agent in Asian countries for centuries to treat cardiovascular diseases, inflammatory diseases, cancers and chronic pain [12,70,80,87,88,91]. The major active components in Bufonis venenum are bufadienolides, such as cinobufagin, bufalin, resibufogenin, cinobufotalin, bufotenine, bufotenidine, and bufobutanoicacid, the first three of which account for approximately 10% of the dry weight of toad venom [43,46,47,84,86]. The antiinflammatory and antinociceptive effects of Bufonis venenum and its purified bufadienolides have been extensively studied over the past years.…”
Section: Introductionmentioning
confidence: 99%
“…Cinobufagin is probably the most abundant bufadienolide in Bufonis venenum and has displayed significant analgesic effect [35,43,46,47,84,86]. Therefore, it was selected in this study to evaluate the antinociceptive effects of Bufonis venenum in cancer pain and explore the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the well-known usage of bufonids in medicinal remedies and the proven pharmacological potential offered by the great chemical diversity of these steroids, the occurrence among species has been summarized (Table S-3). This summary table meets the need for a more complete chemical profile among species of Bufonidae (Gao et al, 2010b;Liu et al, 2014;Zhao et al, 2014).…”
Section: Protease Inhibitor Activitymentioning
confidence: 84%
“…In traditional Chinese medicine, amphibian skin extract has been used for the treatment of different diseases. Previous studies have demonstrated that the major pharmacological constituents derived from toad skins are hydrosoluble indole alkaloids (bufotenine, bufotenidine, and cinobufotenine) and liposoluble steroidal cardiac glycosides mainly composed of bufadienolides 3,4. Bufadienolide-type cardiotonic steroids are a class of C-24 steroids with a characteristic pyrone ring at C-17 and have been identified as major active components and marker compounds of venenum bufonis 5.…”
Section: Introductionmentioning
confidence: 99%